2021
DOI: 10.1007/s00125-021-05398-3
|View full text |Cite
|
Sign up to set email alerts
|

Current and future therapies for type 1 diabetes

Abstract: In type 1 diabetes, insulin remains the mature therapeutic cornerstone; yet, the increasing number of individuals developing type 1 diabetes (predominantly children and adolescents) still face severe complications. Fortunately, our understanding of type 1 diabetes is continuously being refined, allowing for refocused development of novel prevention and management strategies. Hitherto, attempts based on immune suppression and modulation have been only partly successful in preventing the key pathophysiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 145 publications
0
58
0
3
Order By: Relevance
“…The time dependency of ALT is however supported by our previous study, in which long-term prophylactic ALT therapy delayed diabetes onset [ 11 ]. It has been highlighted by this experimental work and by others [ 41 ], that one therapy is unlikely to be effective for T1D prevention. Rather, future work should focus on innovative, combinatorial approaches that could slow β-cell demise and reduce, reset and/or correct immune system function to prolong diabetes remission [ 41 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The time dependency of ALT is however supported by our previous study, in which long-term prophylactic ALT therapy delayed diabetes onset [ 11 ]. It has been highlighted by this experimental work and by others [ 41 ], that one therapy is unlikely to be effective for T1D prevention. Rather, future work should focus on innovative, combinatorial approaches that could slow β-cell demise and reduce, reset and/or correct immune system function to prolong diabetes remission [ 41 ].…”
Section: Discussionmentioning
confidence: 79%
“…Gastric emptying appears to change during disease development in NOD mice and is accelerated at diabetes onset [ 36 ], however in humans, blood glucose elevations in individuals with T1D can slow gastric emptying [ 37 , 38 ] impacting gastrointestinal glucose absorption [ 39 ]. Glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide expression in the gut of NOD mice appear unchanged by hyperglycaemia [ 40 ], and although combinatory therapies with GLP-1 receptor agonists in individuals with T1D have the potential to enhance β-cell function [ 41 ], recent Phase III trials (NCT01836523, NCT02098395) have observed elevations in hypoglycaemia and hyperglycaemia with ketosis [ 42 , 43 ]. One explanation for a rise in glucose concentrations after the OGTT may be that production of proinsulin is contributing to overall increases in insulin at day 75 and to the end of the ALT treatment period, but limited plasma volumes throughout GTTs, prevented proinsulin from being measured.…”
Section: Discussionmentioning
confidence: 99%
“…In turn this limits the ability to monitor the natural history of diabetes development and patient responses to immunotherapy. In addition, although a number of immunomodulatory agents are in clinical trials for type 1 diabetes, these are generally non-specific in their actions (for example targeting CD3 or CD20) (6), and there remains a need to identify and target pathways that are perturbed specifically in islet-antigen specific lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The two most common forms of diabetes, type I (T1D) and type II (T2D), are associated with the eventual loss of insulin-secreting pancreatic β-cells, which can occur either early (T1D) or late (T2D) in disease progression. In the case of T1D, autoimmune destruction results in β-cell death and subsequent insulinopenia, although there is increasing support for the role of β-cell stress in T1D onset ( 10 , 11 ); T2D is characterized by a combination of peripheral insulin resistance and inadequate β-cell compensation, resulting in a metabolic syndrome that leads to eventual β-cell exhaustion and loss of β-cell mass ( 12 , 13 ). T1D and T2D display a multifactorial etiology on both a population and individual level, likely motivated by a complex combination of genetic, epigenetic, and environmental factors ( 14 ).…”
Section: Introductionmentioning
confidence: 99%